2006
DOI: 10.1677/joe.1.06931
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor blockade did not prevent the increase of muscular muscle RING finger-1 and muscle atrophy F-box in arthritic rats

Abstract: Chronic inflammation is associated with a decrease in body weight and cachexia, which is characterized by anorexia and skeletal muscle wasting. The expression of atrogens muscle RING finger-1 (MuRF-1) and muscle atrophy F-box (MAFbx) are increased in muscle atrophy and it is known that tumour necrosis factor (TNF) regulates skeletal muscle loss through TNF receptor p55 (TNFRI). The aim of this study was to examine the effect of polyethylene glycol linked to soluble TNFRI (PEG-sTNFRI) on gene expression of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…However, this does not seem to be the cause, since with systemic anti-TNF-␣ administration, inflammation was also decreased in a similar way (21), but no modifications in IGFBP-5, MAFbx or MuRF1 mRNA, or gastrocnemius weight were observed (22). Taking into account that TNF-␣ is also an important trigger of muscular atrophy and it upregulates MAFbx and MuRF1 gene expression (31,35), the lack of effect of systemic anti-TNF-␣ in preventing muscular wasting was unexpected (22). A possible explanation can be that the "in vivo" anti-TNF-␣ therapy is not able to suppress COX activity in the muscle, as is the case of the synovial tissue from rheumatoid arthritis patients (33).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, this does not seem to be the cause, since with systemic anti-TNF-␣ administration, inflammation was also decreased in a similar way (21), but no modifications in IGFBP-5, MAFbx or MuRF1 mRNA, or gastrocnemius weight were observed (22). Taking into account that TNF-␣ is also an important trigger of muscular atrophy and it upregulates MAFbx and MuRF1 gene expression (31,35), the lack of effect of systemic anti-TNF-␣ in preventing muscular wasting was unexpected (22). A possible explanation can be that the "in vivo" anti-TNF-␣ therapy is not able to suppress COX activity in the muscle, as is the case of the synovial tissue from rheumatoid arthritis patients (33).…”
Section: Discussionmentioning
confidence: 94%
“…These data emphasize the importance of the COX pathway in the inflammatory cachexia. Another explanation could be that muscle proteolysis by the ubiquitin-proteasome pathway is activated by local TNF-␣ rather than by circulating TNF-␣, since systemic anti-TNF-␣ therapy is not able to prevent the increased gene expression of TNF-␣ in the gastrocnemius muscle (22). In the present data, normalization of MuRF1 and MAFbx is associated with a decrease in muscular TNF-␣, which means that there is a relationship between prostaglandin inhibition and TNF-␣ gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…6). However, there is accumulating evidence to suggest that the pathway(s) mediating muscle proteolysis is (are) more complex than anticipated because there are reports showing 1) that IGF-I downregulated the burn-induced elevation of MuRF1 and MAFbx genes independent of its effect on glucocorticoids (40); 2) that IGF-I could not prevent muscle atrophy induced by proinflammatory cytokines, despite inhibiting MAFbx (9); 3) that TNF-␣ blockade did not prevent the increase of muscle MuRF1 and MAFbx genes in arthritic rats (21); and 4) that MuRF1 and MAFbx genes could be regulated through multiple pathways including those involving AKT, NF-B, and p38 MAPK (34). Moreover, as discussed earlier, direct actions of ghrelin on muscle also could have contributed to attenuated expression of the E3 ligase genes and, hence, to reduced muscle proteolysis (10,20,45,51,67).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Granado et al reported the opposite effect of sTNFR1 on arthritic rat. They observed that administration of polyethylene glycol linked-sTNFRI to arthritic rats does not alter the gastrocnemius muscle mass and MuRF1/MAFbx gene expression [125].…”
Section: Anti-tnfsmentioning
confidence: 99%